Social Media Narratives as Political Fan Fiction in the 2016 U.S. Presidential Election - Kolehmainen Pekka (European Association for American Studies, 2022)
In the 2016 election, social media became an increasingly important site for building, transforming, and contesting political narratives. As part of this, the candidates and their supporters engaged in creating and sharing narratives that spanned from an imagined past to the present and onward to an anticipated future. This article examines the transformative processes that took place in social media around these narratives and how they were imbued with fantastic, larger-than-life heroic and villainous properties in a fashion similar to the process of producing fan fiction. Looking at how social media operated as a network of varied public imaginations, the article explores the distinct temporalities around Hillary Clinton, Bernie Sanders, and Donald Trump and explicates how different media logics influenced the ways that the past, the present, and the future were mobilized in narrative formations around each candidate.